2021
DOI: 10.3892/etm.2021.9923
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b inhibits human vascular smooth muscle cell proliferation via targeting the TGF-β/Smad3 signaling pathway

Abstract: Intracranial aneurysms (IAs) are bulges of blood vessels in the cerebral area. The development and progression of IAs are associated with the proliferation of vascular smooth muscle cells (VSMCs) during phenotypic modulation under environmental cues. MicroRNA-29b (miR-29b) has been studied extensively and demonstrated to reduce cell proliferation in various diseases by binding to the 3'-untranslated region (3'-UTR) of a variety of target messenger RNAs (mRNAs), thereby inhibiting their translation. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…As described in previous studies [7], VSMCs trigger stress and injury changes in response to blood pressure by accelerating cell migration and proliferation. Therefore, to investigate the effects of miR-152-3p on cell proliferation and migration, we transfected miR-152-3p mimic and inhibitor in HVSMCs and RT-qPCR confirmed that it was typically up-or down-regulated (p < 0.05, Fig.…”
Section: Mir-152-3p Inhibited the Proliferation And Migration Of Hvsmcssupporting
confidence: 55%
“…As described in previous studies [7], VSMCs trigger stress and injury changes in response to blood pressure by accelerating cell migration and proliferation. Therefore, to investigate the effects of miR-152-3p on cell proliferation and migration, we transfected miR-152-3p mimic and inhibitor in HVSMCs and RT-qPCR confirmed that it was typically up-or down-regulated (p < 0.05, Fig.…”
Section: Mir-152-3p Inhibited the Proliferation And Migration Of Hvsmcssupporting
confidence: 55%
“…miR-29b-2 appears to be mostly associated with a contractile phenotype. It reduced proliferation and migration in human aortic SMCs [26], and inhibiting miR-29b-2 promoted dedifferentiation in human intracranial aneurysm SMCs [27]. It can target Kruppel-like factor 4 (KLF4; a key protein involved in SMC dedifferentiation) [25] and can also target TGFβ [26], a growth factor that can cause ND SV-SMCs to transiently adopt a T2DM SV-SMC phenotype [8].…”
Section: Discussionmentioning
confidence: 99%
“…During this process, a variety of chemokines, chemokine structural analogues, and downstream signals related to the activation of paracrine cytokines contribute to the development or regeneration of VW-S/PCs [57]. Studies have revealed successively that many biochemical cues, such as ERK and PI3K/ AKT signaling, Rac1/Cdc42 signaling pathway, and Wnt and Notch signaling pathway, are involved in the regulation of stem cell migration and differentiation under physiological and pathological condition [57][58][59][60]. For example, Dickkopf-3 (DKK3), a secreted glycoprotein, can activate ERK1/2, PI3K/AKT, Rac1, and RhoA signaling pathways by binding to chemokine (C-X-C motif) ligand 7 (CXCR7), to regulate the migration of Sca-1 + vascular stem cells in the vascular adventitia.…”
Section: Biochemical Signals In the Microenvironment Affecting Vw-s/pcsmentioning
confidence: 99%